Reliabilism and cosmic optimism: situating John Hick in the history of philosophy of religion - Kitta, Naoki (2016)
This dissertation aims to rehabilitate the reasonableness of Hick’s religious pluralism by disclosing the deep structure of his philosophical system. To realize this aim, this dissertation will introduce a new philosophical method of reliabilism, which is proposed by Ernest Sosa and emphasizes total balance and historical maturation. As a result of the introduction of reliabilism, Hick’s philosophical system is disclosed to be composed of Hick’s own philosophy of personhood, combined with the philosophies of Wittgenstein, Kant, and Hume. Instead of emphasizing one of them, this dissertation will propose to read these different components of Hick’s philosophical system as forming a total worldview, which are complementary with each other.